Contemporary advertising and integrated marketing communications - Arens, William F.; Weigold, Michael F. 1958- (New York, NY McGraw-Hill Education, 2021)
"Contemporary Advertising and Integrated Marketing Communications was written for under-graduate students in liberal arts, journalism, mass communication, and business schools. However, because of its practical, hands-on approach, depth of coverage, and marketing management emphasis, it is also widely used in independent schools, university extension courses, and courses on advertising management. The wealth of award-winning advertisements also makes it a resource guide to the best work in the field for students in art and graphic design courses and for professionals in the field"--Provided by publisher.
Previous editions entitled: Contemporary advertising / Courtland L. Bovee.
Includes bibliographical references and indexes.
Keywords: Advertising